Analisis Sistem Pengendalian Internal Persediaan Barang Dagang pada Toko Wijaya Makmur Tabanan - Ni Nyoman Selly Apriantini; Ni Komang Sumadi; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2026)
Inventory of merchandise is an important asset in trading companies that requires an internal control system to minimize the risk of loss. At Wijaya Makmur Store, there has been an increase in the number of inventory losses from 2022 to 2024, amounting to 782 units, 791 units, and 849 units respectively. This condition indicates that internal control over inventory needs to be analyzed to determine its level of effectiveness. This study aims to analyze the implementation of the internal control system over merchandise inventory based on the five components of COSO. This study employs a qualitative descriptive approach, with data acquisition undertaken through documentation, observations, and interviews. The results show that the internal control system has been implemented in accordance with the COSO components; however, there are still weaknesses in the separation of duties and the frequency of stock-taking, which is conducted only twice a year, so the control has not been fully effective in reducing the risk of loss. Therefore, improvements in supervision, better task distribution, and strengthening of control procedures are needed so that inventory management can be more effective